Contextualization of Hadith Ṡaub Al-Syuhrah: Critical Study of The Hijab Outfit of The Day (OOTD) Phenomenon - Hanifah, Jihan Muna; Rachmadhani, Fajar (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2022)
Women in Islam have a special obligation, namely the obligation to wear Hijab. Allah swt ordered it to maintain the dignity of a woman so that no eye would see what a woman should not look at. However, the development of the times affects human lifestyles, especially for Muslimah in hijab, the term hijab OOTD appears. Outfit Out The Day or commonly called OOTD, is an outfit or personal clothing that a person chooses and wears for their daily activities. With that, the OOTD hijab is a hijab that has become a choice and is used by a Muslimah in her daily life, whether she follows the trend or not. The existence of the ṡaub al-syuhrah hadith and the emergence of the OOTD hijab phenomenon are interesting discussions for the author. Through qualitative research with the type of library research and descriptive-analytic analysis, accompanied by takhrij al-hadiṡ and ma'ani al-hadi theories, then the ṡaub al-syuhrah hadith is examined in the context of its writing on the OOTD hijab phenomenon. The existence of the ṡaub al-syuhrah hadith and the emergence of the OOTD hijab phenomenon are interesting discussions for the author. Through qualitative research with library research methods and descriptive-analytic analysis, accompanied by takhrij al-hadiṡ and ma'ani al-hadiṡ theories, then the ṡaub al-syuhrah hadith is examined in the context of its writing on the OOTD hijab phenomenon. The hadith of ṡaub al-syuhrah is assessed as a hasan/ hasan liġairihi hadith and can be used as evidence. Contextualization of the hadith of ṡaub al-syuhrah towards the OOTD hijab phenomenon, namely if it is used with the intention of boasting, takabbur, sum'ah, even to the point of wanting to be praised and seeking popularity, it includes ṡaub al-syuhrah. Whereas the essence of wearing the hijab is that it is adjusted to the syariah and becomes the intention as a cover for the genitals. Therefore, the purpose of this research is to be able to add insight, especially for Muslimah in this era when the OOTD hijab trend is still worn based on the basics of Islamic Syariah.